TUBERCULOSIS DI MASA PANDEMI COVID 19 DALAM PERSPEKTIF ASUHAN KEPERAWATAN KELUARGA - Dwiharini Puspitaningsih; Herman Adidin (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2021)
Success in treating TB patients requires a family role. One of the family roles of tuberculosis patients is fulfilling nutritional needs. this study aimed to provide tuberculosis family nursing care with an inability to maintain nutritional needs. The design used in this research was a case study. The study used 2 families. then diagnosed nursing intervention, implementation and evaluation. Data collection methods by interview, observation, and documentation using the family nursing care format. The results of the assessment of the two families showed the same results, namely were not knowing and were being unable to meet nutritional needs. After conducting three interventions which included counseling and assistance in fulfilling nutritional needs, which was carried out three times, the results were that the family understood and were able to meet the nutritional needs of TB patients. Meeting the nutritional needs of TB patients at home is largely determined by the role of the family.